THE ROLE OF TECHNOLOGY IN IMPROVING MANAGEMENT EFFICIENCY IN ISLAMIC BOARDING SCHOOL - Aprilianto, Moch. Rizwan; Najiburrahman, Najiburrahman; rizal, Mohammad syifaur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Study This aims to study the role of technology in increasing efficiency management in Islamic boarding schools. Focus on the main study. This explores How technology, such as system information, digital management and applications, can improve operational efficiency in managing Islamic boarding schools. The method used in the study is a qualitative approach, with interviews to manage Islamic boarding schools and analyze relevant documents. Research results show that implementation technology can speed up the administrative process, improve transparency in finance, and make communication between administrators and guardians easier. Implications from the study This is that Islamic boarding schools that adopt technology can increase effectiveness and operational efficiency while strengthening their competition in the digital era. Therefore, Islamic boarding schools must keep going, update, and develop infrastructure supporting technology and management.